2014
DOI: 10.1021/jp501629w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Polariton Propagation and Coupling in Gold Nanostructures

Abstract: Surface plasmon polariton (SPP) propagation in chemically synthesized gold nanobars was investigated using scanning transient absorption microscopy. The SPP propagation lengths were correlated to the size and shape of the nanobars, which were determined by atomic force microscopy. The average propagation length was found to be 12 ± 4 μm, and the measured values were independent of the excitation polarization. Finite element calculations were performed for gold nanobars in the presence of a glass substrate to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
94
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(97 citation statements)
references
References 40 publications
3
94
0
Order By: Relevance
“…Control experiments on long nanowires have shown that this effect is not significant in our measurements. [75, 98,177] These experiments also show that the finite group velocity of the SPP does not create a problem.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Control experiments on long nanowires have shown that this effect is not significant in our measurements. [75, 98,177] These experiments also show that the finite group velocity of the SPP does not create a problem.…”
Section: Resultsmentioning
confidence: 66%
“…[181,182] The finite element analysis shows that the propagation lengths are very sensitive to the nanowire dimensions, and factors such as the aspect ratio and degree of rounding at the corners of the structure. [177] The comparison between experiment and simulation demonstrates that, in general, both the bound and leaky modes are excited by the pump laser. The transient absorption measurements provide information about the mode that has the longest propagation length, which could be either the bound or the leaky mode.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations